Unique Structural Features of Membrane-Bound C-Terminal Domain Motifs Modulate Complexin Inhibitory Function - Snead, David; Lai, Alex L.; Wragg, Rachel T.; Parisotto, Daniel A.; Ramlall, Trudy F.; Dittman, Jeremy S.; Freed, Jack H.; Eliezer, David (Frontiers in Molecular Neuroscience, 2017)
Complexin is a small soluble presynaptic protein that interacts with neuronal SNARE proteins in order to regulate synaptic vesicle exocytosis. While the SNARE-binding central helix of complexin is required for both the inhibition of spontaneous fusion and the facilitation of synchronous fusion, the disordered C-terminal domain (CTD) of complexin is specifically required for its inhibitory function. The CTD of worm complexin binds to membranes via two distinct motifs, one of which undergoes a membrane curvature dependent structural transition that is required for efficient inhibition of neurotransmitter release, but the conformations of the membrane-bound motifs remain poorly characterized. Visualizing these conformations is required to clarify the mechanisms by which complexin-membrane interactions regulate its function. Here we employ optical and magnetic resonance spectroscopy to precisely define the boundaries of the two CTD membrane-binding motifs and to characterize their conformations. We show that the curvature dependent amphipathic helical motif features an irregular element of helical structure, likely a pi-bulge, and that this feature is important for complexin inhibitory function in vivo.